The CELTA course. Trainee book Certificate in English Language Teaching to Adults - Thornbury, Scott; Watkins, Peter (Cambridge Cambridge University press, 2007)
The CELTA course provides full coverage of the CELTA syllabus in a ready to use course.
Contents.
Keywords: Teaching; English - foreign language